Prediction the Behavior of Piles in Clayey Soils - Adnan Hasan, Hanan (International Journal of Engineering and Technology, 2018)
This research includes a non- linear finite element analysis of axisymmetric soil-pile system. The analysis included piles of different length and diameter. The interface element was used as a thin layer separating the pile from surrounding soil. The load settlement curves for piles installed in soft to medium and stiff clays were obtained. Two consideration were studied; the ultimate capacity of pile and the settlement reduction factor. The results show that increase in the length and diameter of pile leads to increase in the ultimate load in range (35- 60%) and in the range (33- 35) % respectively. The distribution of lateral displacement along the depth of the pile gave the same trend in both soft to medium and stiff clay while the settlement reduction factor in soft soil is greater than for the stiff clay. Â Â Â